632 PREVALENCE OF VARIANT GENOTYPE IN PATIENTS WITH SUSPECTED CARDIAC ATTR AMYLOIDOSIS. (15th December 2022) - Mussinelli, Roberta; Milani, Paolo; Casarini, Simona; Nuvolone, Mario; Fabris, Francesca; Perlini, Stefano; Merlini, Giampaolo; Palladini, Giovanni; Obici, Laura
Abstract: Background: Emerging therapeutic options and availability of non-invasive diagnostic tools are increasing recognition of cardiac ATTR (transthyretin) amyloidosis worldwide. However, the relative prevalence of hereditary ATTR amyloidosis may be underestimated, particularly in aged males in whom the disease may be assumed to be wild- type and TTR genetic test not performed. TTR gene variants associated with a predominant cardiac phenotype are known to result in worse prognosis. Identification of a pathogenic variant may not only guide treatment strategy but also allow for genetic counselling and cascade testing in at risk relatives. Purpose: To identify the prevalence and type of genetic mutations in patients referred to our Centre for suspected cardiac ATTR amyloidosis. Methods: We evaluated consecutive patients referred to our Centre from January 2017 to December 2021 for suspected cardiac ATTR amyloidosis based on signs of heart involvement on echocardiogram or magnetic resonance, a Perugini score 2 or 3 bone scintigraphy or a tissue biopsy proving TTR amyloid deposition, no family history, no signs of neurological or other organ involvement. All patients underwent clinical evaluation and laboratory analysis including serum and urine immunofixation, serum free light chains, and TTR genetic testing. As AAPOA-I amyloidosis is reported in Northern Italy we also routinely perform APOA1 genetic test in patients with suspected cardiac amyloidosis. Diagnosis was ultimately established on a tissue biopsy in patients in which a monoclonal component (CM) was identified. Results: 481 patients were included, mean age at presentation was 76 years (min-max 50-93), 40 (8%) were women. In all patients with CM (29%), tissue biopsy confirmed TTR amyloid deposition by immunoelectron microscopy or proteomics. 439 patients (91%) did not carry TTR or APOA1 variants, while 42 (9%) had a heterozygous pathogenic mutation. 41 patients have a pathogenic TTR mutation the most frequent being Ile68Leu (n=28; 67%), followed by Tyr78Phe, Val122Ile and Val94Leu (n=3/2/2 respectively). One novel mutation, namely Pro43Thr, was identified. In one patient APOA1 Leu75Pro variant was identified and diagnosis of AApoA-I amyloidosis confirmed by typing on endomyocardial biopsy. No significant differences were found between ATTRwt and ATTRv patients apart from gender distribution. Although age did not differ among the two groups, the prevalence of a variant genotype raises when considering only patients younger than 70 years (14%). 20% of women carry a pathogenic variant, irrespective of age. Interestingly, among women with ATTRwt (n=32), almost one third (31%) was diagnosed with hip dysplasia in childhood, requiring multiple orthopaedic surgeries and prothesis implantation. Conclusions: In our cohort, one out of ten patients referred for suspected cardiac ATTR amyloidosis was ultimately diagnosed with ATTRv. Our results emphasize the importance of performing genetic testing irrespective of age at presentation. Diagnosis of ATTRv is relevant for monitoring disease progression, for defining treatment strategy and for offering genetic counselling and presymptomatic test in at risk relatives. Finally, the high prevalence of hip dysplasia among women with ATTRwt deserves further investigation to define whether it may represent a novel, gender-related red flag for this disease.